Feasibility study on SMS and e-mail current awareness service for the St. Luke's Medical Library - Palac, Catherine Y. (2009)
The expanding knowledge of medicine leads to the growing information needs of medical practitioners, researchers and medical students. Because of this, there should be a great improvement on the means by which updates like new breakthroughs, discoveries of new diseases and drugs to treat them, can be disseminated. To support the needs of the library users, medical libraries provide services that would notify them about the current information about the library which is known as Current Awareness Service (CAS). Today, some of the technologies that are commonly used by most library users are the mobile phone and electronic mail (email).